Synthesis and estimation of copper nanoparticles as agrochemicals against phytophthora spp - Cao , Van Du; Nguyen, Van Thanh Dat; Thai , Minh Tien; Duong , Thi Ngoc Dung; Nguyen, Xuan Chuong; Nguyen , Thi Phuong Phong; Nguyen, Huu Tri (Journal of Technical Education Science, 2018)
Nanoparticles have been extensively in recent years. The effective applications of nanoparticles depend on their sizes. Copper nanoparticles (CuNPs) are among metal nanoparticles which have been reported by many researchers. In this work, CNPs have been synthesized from copper sulfate via chemical reduction method in the presence of trisodium citrate dispersant and polyvinylpyrrolidone (PVP) as protecting agents. The colloidal CuNPs were characterized by using UV–Visible spectroscopy, transmission electron microscopy (TEM), and X-ray diffraction (XRD) techniques. By using a certain amount of materials which has been described in literatures, the size of CuNPs obtained within a range of 4-20 nm in diameter. The colloidal solution of CuNPs was investigated the potential against Phytophthora spp. which cause economically crop diseases. Under in vitro test conditions, the inhibition of Phytophthora spp. mycelia growth at three concentrations of CuNPs (10, 20, 30 ppm) after 48 hours are 90.18%, 91.87% and 100%, respectively. These results provided a simple and economical method to develop the CuNPs-based-fungicide.